PENINGKATAN PENGETAHUAN SISWA SD SEBAGAI TIM PEMANTAU JENTIK DI NEGERI ASSILULU - Tina Amnah Ningsih; Farha Assagaff (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
Dengue hemorrhagic fever is a disease caused by the dengue virus, which is transmitted through the Aedes aegypti mosquito vector. An effort to eradicate mosquito nests (PSN) is carried out so that the larva-free rate can be achieved 95%. The purpose of this activity is to increase the knowledge of elementary school students and increase the larva-free rate in Assilulu Country. The method used is counseling about Aedes aegypti mosquito larvae using lecture methods and animated videos. This activity was carried out through several stages, namely, counseling about Aedes aegypti mosquito larvae, forming a larva monitoring team, larva monitoring activities, and evaluating larva monitoring activities. The results achieved in this program are an increase in the knowledge of elementary school students about dengue and the Aedes aegypti mosquito and an increase in ABJ in Assilulu Village